Practice of the psychological emergency from gestalt therapy - Raymundo Villalva, Ornella (2023)
Psychological intervention played an important role during the pandemic, due to the emergence of emotional problems such as anxiety, anguish and depression. In the present study, Virtual Psychological Emergency (PE) is analyzed, from Gestalt therapy perspective. The phenomenological method was used to describe experiences of ten of the emergency psychologists who attended during the first months of confinement (march - July 2020) and offered free virtual assistance to people with emerging emotional needs, coming from various countries in America. Latin. We conclude with the identification of a GP practice as a bilateral learning, use of the epoché, resonances, technical resources and Yo-Tú encounter. Likewise, the presence of the altruistic attitude is rescued and the practice of a GP is validated as a form of intervention in the promotion, care and prevention of mental health.